ECML PKDD 2018 Workshops: MIDAS 2018 and PAP 2018, Dublin, Ireland, September 10-14, 2018, Proceedings - Alzate, Carlos; Monreale, Anna; Bioglio, Livio; Bitetta, Valerio; Bordino, Ilaria; Caldarelli, Guido; Ferretti, Andrea; Guidotti, Riccardo; Gullo, Francesco; Pascolutti, Stefano (Lecture Notes in Computer Science, 2019)
This book constitutes revised selected papers from two workshops held at the 18th European Conference on Machine Learning and Knowledge Discovery in Databases, ECML PKDD 2018, in Dublin, Ireland, in September 2018, namely:MIDAS 2018 - Third Workshop on Mining Data for Financial Applications andPAP 2018 - Second International Workshop on Personal Analytics and Privacy.The 12 papers presented in this volume were carefully reviewed and selected from a total of 17 submissions.